The Impact of Risk Attitudes on Financial Investments - Walter Hyll; Maike Irrek (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2015)
Several scholars analyze the relationship between individuals' willingness to take risks and financial investment decisions. We add to this literature in using data from the German Socio-Economic Panel which allow ruling out that investments in risky assets itself impact on risk attitudes. We show that individuals with a higher willingness to take risks are more likely to hold bonds, stocks, and company assets. When grouping individuals into risk groups, our results reveal that high risk takers are also less likely to own a life insurance. If endogenous adaption of risk attitudes from holding assets in previous years is not taken into account, the impact of risk attitudes on holding risky assets is upward biased.
urn:nbn:de:gbv:3:2-48596
Keywords: D14; D81; G11; 330; risk attitudes; financial investment; portfolio choice; reverse causality; German Socio-Economic Panel